1981
DOI: 10.1159/000212493
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Salicylate Metabolites with Age in Patients Receiving Chronic Acetylsalicylic Acid Therapy

Abstract: A high pressure liquid chromatographic method was used to measure the serum concentrations of salicylic, salicyluric and gentisic acids in patients receiving chronic acetylsalicylic acid therapy. There was good correlation between this method and the established colorimetric assay for salicylic acid. The concentration of gentisic and salicyluric acids were increased in patients older than 60 years. No correlation was found with sex, concomitant ingestion of other drugs, serum creatinine or serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…On the other hand, salicyluric acid plasma concentrations appeared to be significantly higher in the elderly than in the young subjects, which is in good agreement with the results of Montgomery & Sitar (1981). Similar to the finding of a recent study (Gunsberg et al, 1984), a correlation was found between the renal clearance of salicyluric acid and creatinine clearance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, salicyluric acid plasma concentrations appeared to be significantly higher in the elderly than in the young subjects, which is in good agreement with the results of Montgomery & Sitar (1981). Similar to the finding of a recent study (Gunsberg et al, 1984), a correlation was found between the renal clearance of salicyluric acid and creatinine clearance.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Salem & Stevenson (1977) found that the AUC of salicylate for elderly subjects was approximately twice that for young subjects. Recently, Montgomery & Sitar (1981) found higher steady-state plasma levels of salicyluric acid, a major metabolite of salicylate, in elderly patients receiving chronic ASA therapy. In addition, the metabolism of salicylate appears to be influenced by genetic factors (Furst et al, 1977), and plasma concentrations of ASA and salicylate have been found to be consistently higher in female than in male subjects (Coppe et al, 1981; Kelton et al, 1981;Buchanan et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that plasma concentrations of gentisic and salicyluric acids are significantly increased in patients over 60 years of age (Montgomery and Sitar, 1981). Further studies are obviously indicat~d to elucidate the possible correlation between altered disposition of salicylate and the propensity of geriatric patients to salicylism.…”
Section: Salicylatementioning
confidence: 98%
“…Salicylic acid in plasma was measured by the h.p.l.c. method of Montgomery & Sitar (1981 For in vivo studies, pooled plasma from a different panel of normal volunteers was used to study the effects of salicylic acid (100 mg/l) on plasma protein binding of isoxicam 5 to 20 mg/l added in vitro. For ex vivo studies, plasma obtained from the 10 volunteers in the isoxicam-ASA kinetic study was used.…”
Section: Introduction Methodsmentioning
confidence: 99%